Blue Economy - Prospects & Challenges for Pakistan - Khan (R), Cdr Anees Muhammad (Journal of Nautical Eye and Strategic Studies, 2025)
This study explores the Blue Economy: Prospects and Challenges for Pakistan, emphasizing the sustainable use of maritime resources for economic development and national security. It reviews global best practices, highlights the significance of equitable access to resources, and examines Pakistan’s key maritime sectors shipping, seafood, maritime infrastructure, coastal tourism, and resource exploration within the Exclusive Economic Zone (EEZ). Anchored in Structural Realism, the research argues that strengthening the blue economy is essential for reducing Pakistan’s economic vulnerabilities and enhancing state power in a competitive geopolitical environment. Employing a predominantly qualitative approach, supported by relevant quantitative data, the study underscores the need for Pakistan to shift from a land-centric to a maritime-focused development model. Strategic recommendations call for policy reforms, investment in maritime industries, and integration of the Blue Economy into national plans like Vision 2025. A comprehensive framework combining environmental, social, and political considerations is vital for sustainable outcomes. Ultimately, the paper concludes that strong political will and regional cooperation are key to unlocking Pakistan’s maritime potential and achieving long-term economic resilience and security.